2018
DOI: 10.1167/iovs.18-25032
|View full text |Cite
|
Sign up to set email alerts
|

OCT Angiography and Cone Photoreceptor Imaging in Geographic Atrophy

Abstract: PurposeTo compare cone spacing and choriocapillaris (CC) perfusion adjacent to geographic atrophy (GA) in patients with age-related macular degeneration (AMD) and age-similar normal eyes.MethodsSubjects were imaged using adaptive optics scanning laser ophthalmoscopy (AOSLO), fundus autofluorescence (FAF), and swept-source optical coherence tomography angiography. The GA border was identified using FAF images; CC flow void was analyzed in 1° regions extending from the GA border. A grader masked to CC perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Moreover, the area surrounding the GA margin was shown to reveal a significantly higher flow impairment compared to more eccentric areas in the same eye. These findings indicate that choriocapillaris degeneration may occur before the development of GA [30,31,[45][46][47][48]. Innovative adaptive optics investigations revealed that this choriocapillaris hypoperfusion even extended the region of increased cone spacing, an early sign of atrophic retinal processes [47].…”
Section: Application Of Oct-a In Gamentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, the area surrounding the GA margin was shown to reveal a significantly higher flow impairment compared to more eccentric areas in the same eye. These findings indicate that choriocapillaris degeneration may occur before the development of GA [30,31,[45][46][47][48]. Innovative adaptive optics investigations revealed that this choriocapillaris hypoperfusion even extended the region of increased cone spacing, an early sign of atrophic retinal processes [47].…”
Section: Application Of Oct-a In Gamentioning
confidence: 76%
“…These findings indicate that choriocapillaris degeneration may occur before the development of GA [30, 31, 45-48]. Innovative adaptive optics investigations revealed that this choriocapillaris hypoperfusion even extended the region of increased cone spacing, an early sign of atrophic retinal processes [47]. Thereby, choriocapillaris flow and structure might be potential therapeutic targets and/or susceptible early surrogate markers, possibly before the point of no return.…”
Section: Application Of Oct-a In Gamentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how the different models deal with this blur and the impact on performance should be considered in future studies. Also, future studies should evaluate the proposed method on datasets from pathological eyes, as many diseases can change the mosaic structure significantly,14 as well as with other imaging modalities such as dual split and confocal 24. Whether similar performance can be achieved with datasets from pathological eyes remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these cells serve daylight and color vision. Diseases such as Stargardt's disease,1 retinitis pigmentosa,2 choroideremia,3 and macular degeneration4 are characterized by the loss of photoreceptors leading to impaired vision. A way to image the photoreceptor array is using an adaptive optics scanning laser ophthalmoscope (AOSLO).…”
Section: Introductionmentioning
confidence: 99%